Learning Strategies at Pembelajaran SMA Muhammadiyah 4 Surabaya During Pandemic Covid 19 - Raeyen Anggara Putra (International Consortium of Education and Culture Research Studies, 2021)
This research is intended to know what the learning strategy that been used in SMA Muhammadiyah 4 Surabaya when in this pandemic. This research uses the Descriptive research method and interview method to get the data .SMA Muhammadiyah 4 Surabaya still used an online learning and they also used Online Registration for a new student, the learning processes have an advantage. And for the school life there are only school’s staff for example there are teacher in faculty office but not so many, and there are administration staff in administration room, and for the students, there are no students cause they are learning at home.